Penggunaan Media Wordwall untuk Meningkatkan Hasil Belajar IPAS Kelas 5 di SD Negeri 02 Taman - Andik Prasetiyiawan; Vivi Rulviana; Rakini Rakini (Journal Innovation In Education, 2024)
The purpose of this study is to investigate how fifth-grade students at SD Negeri 02 Taman can improve their learning results in the Natural and Social Sciences (IPAS) course by using Wordwall medium. The poor interest and engagement of students in traditional learning methods is the background of this study. Using direct observation over a four-week period, the study technique used a qualitative approach with a descriptive design to evaluate student interactions and the learning environment in the classroom. The findings of the investigation showed that using Wordwall considerably raised students' excitement, involvement, and engagement in the classroom. Students also showed that they understood the content being taught better. The research's conclusions highlight how crucial it is to use interactive learning resources in elementary school to foster a more interesting and effective learning environment. Therefore, Wordwall can be a useful tool for improving student results and the quality of instruction while promoting creativity in the classroom in the digital age.